Development of AI-Based Interactive Accounting E-Modul Media Chatbot in Increasing Student Learning Interest - Novi Zamtina; Agus Susilo (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research aims to develop interactive e-Modul media based on AI Chatbot for accounting subjects and evaluate its impact on students' learning interests. Qualitative methods are used through in-depth interviews with teachers and students as well as classroom observations using the E-Module. The results showed that this interactive e-Modul was well received by teachers and students, with a significant increase in student participation and enthusiasm. Students feel more motivated and helped in understanding accounting material, while teachers feel helped by Chatbots that provide quick and accurate answers. Although there are several technical obstacles, such as limited Chatbot knowledge and access problems, the results of this study indicate that the use of an AI-based interactive e-Modul Chatbot has great potential to increase student learning interest. Continuous development and support of adequate technology infrastructure are needed to optimize the implementation of this learning media in the future.